Tissue origin dictates functional diversity of BMSC-derived EVs in bone regeneration - Wang, Jia; Hong, Jinjia; Tian, Chunrui; Zhao, Xiangyu; Xie, Qingpeng; Li, Na; Zhang, Yuan; Liu, Meixian; Zhang, Pengfei; Xing, Helin; Wang, Lu; Wang, Xing (Frontiers in Cell and Developmental Biology, 2025)
Bone regeneration is mediated by paracrine signaling, with extracellular vesicles (EVs) playing a crucial role as communication mediators. Previous studies have shown that there are differences in the performance of the bone marrow mesenchymal stem cells (BMSCs) derived from the mandible and limbs. However, it is not clear whether there are differences in EVs originating from them. In this study, we demonstrated that compared to EVs derived from limbs, the EVs derived from the mandible were more effective in stimulating BMSCs migration, proliferation, osteogenic differentiation in vitro, and bone regeneration in vivo. Upregulated miRNAs in EVs from mandible target signaling pathways such as MAPK, Wnt, and Hippo, which have been shown to be crucial for bone formation. Therefore, it may be an excellent candidate for improving bone healing in autologous bone transplantation, bone tissue engineering, or other bone diseases.